Identifikasi Senyawa Hasil Pirolisis Sampah Plastik Polietilen (PET) dan Polietilen berlapis logam (Metallized PET foil) - Fannyda, Raidatul; Nursaadah, Euis; Ruyani, Aceng (PendIPA Journal of Science Education, 2024)
Indonesia is the second largest contributor of plastic waste in the world with an unmanageable capacity of 3.2 million tonnes each year and 1.29 million tonnes of plastic waste ending up in the ocean. Plastic waste accounted for 16% of the world's marine plastic pollution, which directly contributed greenhouse gas emissions and climate change. Pyrolysis was an effective solution to overcome the processing of plastic waste which produces energy conversion. Pyrolysis is the process of breaking down long chain polymer molecules into smaller molecules through thermal cracking in the absence of oxygen at temperatures above 400°C. Pyrolysis does not release pollutants in the form of particles and CO2 into the atmosphere so it practically does not disturb the environment. This research method was a pyrolysis experiment on Polyethylene terephthalate (PET) plastic waste from mineral water packaging and metal-coated PET (metallized PET foil) from milk and snack packaging. The pyrolysis product was liquid oil with two different types of colors whose compounds were identified using gas chromatography – mass spectrometry (GC-MS). The number of compound components from PET plastic waste pyrolysis products was 58 components with the largest compound component areas being 5-methyl-1-heptene and 1-tridecanol. Meanwhile, the number of compound components from the pyrolysis product of metal-coated PET plastic waste (metallized PET foil) was 56 compound components with the largest compound component areas being 3-methyl-5-undecene and 1-tridecanol.